Inflationary memory as restrictive factor of the impact of the public expense in the economic growth: Lessons from high inflation Latin American countries using an innovative inflationary memory indicator - Ernesto Sheriff (Institute for Advanced Development Studies (INESAD), 2010)
A new inflationary memory indicator was developed and applied here. A panel was built with the selected countries considering the economic growth as dependent variable in function of the convergence hypothesis, the inflation rate, the public expense and, the recursive variance of the inflation (VARINF) as inflationary memory indicator. The expected results of the panel were that the inflation and their variability affect the growth negatively neutralizing the possible effects that it could have the public expense on the same one. Five Latin American countries with experiences of high inflation were included (Argentina, Brazil, Bolivia, Peru and Nicaragua).
Keywords: E31; E65; D87; N16; 330